Kemampuan Literasi Dan Numerasi Dengan Pendekatan Realistic Mathematics Educations (RME) Pada Materi Perbandingan Trigonometri - Suryadi, Suryadi; Jana, Padrul; Sagita, Laela; Marsiyam, Marsiyam; Triyadi, Totok; Saefudin, Abdul Aziz; Ratini, Ratini (Universitas Pekalongan, 2024)
The purpose of this study is to improve mathematics learning outcomes literacy and numeracy skills by using a realistic mathematics education (RME) approach, especially trigonometry comparison material of SMA Muhammadiyah Imogiri. Students of grade X E1 SMA Muhammadiyah Imogiri are the main objects involved in this research. This RME approach model is used as a strategy to improve students' literacy and numeracy skills about trigonometric comparison material. The results of this study show that applying the RME approach is very effective because students are able to apply contextual problems related to trigonometric comparisons and are able to develop their own discipline and mutual cooperation attitudes, the significance of mastering students' literacy and numeracy skills in applying and solving contextual problems in trigonometric comparisons. Based on a sample of 24 students of grade X E1, it is proven that more than 80% of students are complete and able to apply contextual problems in trigonometric comparisons, while less than 15% of students are incomplete and unable to apply contextual problems.